From Pavement to Population Genomics: Characterizing a Long-Established Non-native Ant in North America Through Citizen Science and ddRADseq - Zhang, Yuanmeng Miles; Vitone, Tyler R.; Storer, Caroline G.; Payton, Adam C.; Dunn, Robert R.; Hulcr, Jiri; McDaniel, Stuart F.; Lucky, Andrea (Frontiers in Ecology and Evolution, 2019)
Clarifying the population structure and introduction history of non-native species is essential to preventing and mitigating effects of invasion, yet the invasion history of many long-established non-native species remain poorly understood. This study characterized the population structure of one of the most commonly encountered urban ants in North America using public participant-collected specimens and double-digest restriction-site associated DNA sequencing (ddRADseq). Based on this genomic approach we confirm the identity of populations ranging across the continent as Tetramorium immigrans Santschi, and report low genetic diversity across its range, suggesting that this entire population resulted from the establishment of one single, or few closely related ant colonies, approximately two hundred years ago. The absence of strong population structure suggests that this ant’s spread across North America has been repeatedly aided by human-assisted dispersal. We find no evidence of inbreeding in T. immigrans; contrasts with the inbreeding and unicoloniality of many other invasive ants. These results demonstrate how collections-based public participatory science and emerging high-throughput sequencing techniques each have the potential to vastly improve the amount of data available to researchers; together, these techniques can be deployed to address ecological and evolutionary questions in non-model organisms, including invasion biology. We suggest that this model is particularly well suited for research on common taxa that are ecologically important but poorly understood.